Anatomy of a Coup: How CIA Front Laid Foundations for Ukraine War - Klarenberg, Kit (Kit’s Newsletter, 2022)
Obvious examples of Central Intelligence Agency covert action abroad are difficult to identify today, save for occasional acknowledged calamities, such as the long-running $1 billion effort to overthrow the government of Syria, via funding, training and arming barbarous jihadist groups.